Setting and Reaching Targets with Computer-Assisted Cochlear Implant Fitting - Bart Vaerenberg; Geert De Ceulaer; Zoltán Szlávik; Patrizia Mancini; Andreas Buechner; Paul J. Govaerts (The Scientific World Journal)
Objective. The paper aims to demonstrate the feasibility of defining a substantial set of psychoacoustic outcome measures with preset targets and to adopt a systematic methodology for reaching these targets in a large group of subjects, by more than one clinical centre. Design. Retrospective data analysis. Setting. Multicentre with 14 participating centres. Patients. 255 adults and children using the Advanced Bionics HiRes90k cochlear implant. Intervention. Target driven fitting with the fitting to outcomes expert (FOX) system. Main Outcome Measures. For each patient, 66 measurable psychoacoustical outcomes were recorded several times after cochlear implantation: free field audiometry (6 measures) and speech audiometry (4), spectral discrimination (20), and loudness growth (36), defined from the A§E test battery. These outcomes were reduced to 22 summary variables. The initial results were compared with the latest results. Results. The state of the fitting process could be well monitored by means of the measured variables. The use of the FOX computer assisted CI-programming significantly improved the proportion of the 22 variables on target. When recipients used the automated MAPs provided at switch-on, more than half (57%) of the 22 targets were already achieved before any further optimisation took place. Once the FOX system was applied there was a significant 24% (P<0.001) increase in the number of targets achieved. Conclusions. This study demonstrates that it is feasible to set targets and to report on the effectiveness of a fitting strategy in terms of these targets. FOX provides an effective tool for achieving a systematic approach to programming, allowing for better optimisation of recipients' MAPs. The setting of well-defined outcome targets allowed a range of different centres to successfully apply a systematic methodology to monitoring the quality of the programming provided.